Investigation of the Mechanical and Permeability Evolution Effects of High-Temperature Granite Exposed to a Rapid Cooling Shock with Liquid Nitrogen - Tianzuo Wang (Hindawi-Wiley, 2021)
Liquid nitrogen (LN2), which can greatly improve the efficiency of hot dry rock (HDR) mining, is commonly used as a cooling material in the enhanced geothermal system (EGS). Physical property, triaxial compression, and permeability tests were undertaken on treated granite samples, for a better scientific understanding of the effect of the LN2 cooling method on the mechanical and permeability properties of the rocks after heat treatment. The experimental results indicated that the physical properties of the treated granite change significantly, such as the density and wave velocity are substantially reduced. Meanwhile, with the increase of treatment temperature, the macroscopic cracks on its surface are gradually generated and the volume is expanded clearly. In addition, the surface wettability of granite gradually increases with increasing temperature. Compared with the air/water cooling methods, under LN2 cooling condition, the mechanical properties decrease markedly. When the temperature exceeds 600°C, the granite strength decreases significantly to only 56.16% of the reference value. The deformation properties also change significantly, with a final strain of about 3% at failure for a sample at 800°C, showing an obvious ductile deformation characteristic. Further, an appreciable correlation also exists between the initial permeability of granite and temperature. Once the temperature exceeds 200°C, the increase in temperature contributes to the increase in initial permeability. In addition to the effect of temperature, the increase in load also leads to a change in the permeability coefficient. When the temperature reaches 600°C, the permeability of granite first decreases and then increases with the increases in axial stress. The results of this paper are valuable in understanding the effect of thermal shock by LN2 on the fracturing efficiency and permeability characteristics of dry hot rocks.